2005
DOI: 10.1177/000312240507000606
|View full text |Cite
|
Sign up to set email alerts
|

Interpreters of the Literary Canon and Their Technical Instruments: The Case of Balzac Criticism

Abstract: International audienceDrawing insights from the ethnographies in the natural sciences, which have focused on the role of technical instruments in laboratory practices, this article asks, "What role do technical instruments play in the humanities?" Editions of La Comédie humaine, written by Honoré de Balzac, are taken as a case study. Primarily based on ethnographic research with Balzac scholars, this article traces the evolution of Balzac's text from a unified and unadorned text in the 1930s, to a single annot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Other approaches have directed methods and theories in the sociology of science to analyses of knowledge production in a wide array of disciplines. For example, Grégoire Mallard (2005) focused on the role of ‘technical’ instruments in literary studies, focusing on the case of critics of Honoré de Balzac. Mallard observed that literary scholars who adapted electronic editions of classical French texts forwarded new critical interpretations of the literature, which entertained an ‘elective affinity’ with the annotated editions made possible by electronic publishing.…”
Section: Recent Movesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other approaches have directed methods and theories in the sociology of science to analyses of knowledge production in a wide array of disciplines. For example, Grégoire Mallard (2005) focused on the role of ‘technical’ instruments in literary studies, focusing on the case of critics of Honoré de Balzac. Mallard observed that literary scholars who adapted electronic editions of classical French texts forwarded new critical interpretations of the literature, which entertained an ‘elective affinity’ with the annotated editions made possible by electronic publishing.…”
Section: Recent Movesmentioning
confidence: 99%
“…However, scholars interested in the social construction of social‐scientific and humanistic knowledge have successfully adapted theories and methods from the sociology of science to analyze knowledge processes outside of science, such as the critical interpretation of French literature, the legitimation of theories in French and German philosophy, and peer evaluation in the social sciences and humanities (see, e.g., Guetzkow et al. 2004; Kusch 1995; Lamont 1987; Mallard 2005). By adapting the methods of the sociology of science to study knowledge production in the humanities and social sciences, sociologists are better able to distinguish between knowledge processes that are specific to the sciences and those existing in other institutionalized research fields.…”
mentioning
confidence: 99%
“…Third, though the Bayesian framework is quite popular in statistics, social scientists are still inclined to apply frequentist interpretations to their analyses. For example, in reviewing Volume 70 (2005) of the American Sociological Review, only 3 out of 29 articles using inferential statistics made explicit use of a Bayesian approach (Cole 2005; Karinek et al 2005; Mallard 2005). 14 Thus we appeal to the more common frequentist framework in considering the conditions necessary to alter an inference.…”
Section: A Bayesian Motivation For the Indicesmentioning
confidence: 99%
“…Social scientists have focused on microsocial processes of knowledge construction in contexts as varied as science labs, literary seminars, and peer evaluation committees (Knorr Cetina, 1999; Mallard, 2005). Karin Knorr Cetina (1999) argued for “epistemic culture” as a substitute for “discipline,” to emphasize how scholars engaged in a common research task form a group culture of knowledge, defined by a shared system of referents and not by institutional or external factors.…”
Section: The Sociology Of Knowledge In Contextmentioning
confidence: 99%
“…Research on the emergence of new academic fields focuses on how proponents forge institutional niches for new programs, with broad emphasis on how institutional conditions and processes reflect the content of knowledge (Camic, 1995; Rojas, 2007; Small, 1999). Studies of the routines and practices of knowledge-making have focused on particle physics labs, molecular biology labs, and literary seminars, with less emphasis on new disciplines or fields with politicized origins (Guetzkow, Lamont, & Mallard, 2004; Knorr Cetina, 1999; Mallard, 2005). A combined approach that draws on narratives of institutionalization and accounts of knowledge-making forms my analytic framework.…”
mentioning
confidence: 99%